Pomegranate (Punica granatum L) powder reduced malondialdehyde (MDA) level in cigarette smoke exposed rats (Faculty of Medicine Universitas Indonesia, 2011)
Background: To analyze the effect of pomegranate (P. granatum) powder consumption for 14 days on lipid peroxidation as shown by malondialdehyde (MDA) level in cigarette smoke exposed rats. Methods: Thirty Sprague-Dawley male rats were randomly divided into three groups, i.e.: a control group and two treatment groups. The treatment groups either received 5% (R1: 0.351% flavonoids/100g) or 10% (R2: 0.566% flavonoids/100g) pomegranate extract powder, respectively. The diets in the form of pellets were freely consumed (ad libitum) and were given for 14 days. Rats were exposed to cigarette smoke three times per day. Blood samples were taken on day 0, day 8th and 15th for MDA analyses. Comparison of MDA levels was done by ANOVA's test on normal data. Results: On day 0, the MDA levels were 0.35±0.06 nmol/mL, 0.38±0.06 nmol/mL and 0.38±0.06 nmol/mL for control, 5% and 10% pomegranate powder group, respectively (P=0.65). On day 8th, the MDA levels were 0.70±0.06 nmol/mL, 0.57±0.06 nmol/mL and 0.56±0.06 nmol/mL, and on day 15th, the MDA levels were 1.02 ±0.06 nmol/mL, 0.89±0.06 nmol/mL and 0.80±0.06 nmol/mL in control, 5% and 10% pomegranate powder group, respectively. There was a signifi cant difference (P< 0.001) in MDA levels on day 8th and 15th between groups. The average MDA level for rats consuming control diet was the highest on day 8th and 15th. On the other hand, the lowest average MDA level on day 8th and 15th was observed in rats given 10% pomegranate extract powder. In comparison to MDA level before cigarette smoke exposure, the increases in MDA levels for rats consuming control diet, 5% and 10% pomegranate extract powder were 97%, 52% and 48% on day 8th, and 187%, 137% and 113% on day 15th, respectively. The highest increase in MDA level was observed in control group. Conclusion: The use of pomegranate powder at 5% and 10% concentration was able to prevent the occurrence of lipid peroxidation as shown by the MDA levels and the effect was dose dependent. (Med J Indones 2011; 20:34-9) Keywords: antioxidant, flavonoids, lipid peroxidation